2017
DOI: 10.1115/1.4037624
|View full text |Cite
|
Sign up to set email alerts
|

Rotordynamics Performance of Hybrid Foil Bearing Under Forced Vibration Input

Abstract: Foil bearings (FB) are one type of hydrodynamic air/gas bearings but with a compliant bearing surface supported by structural material that provides stiffness and damping to the bearing. The hybrid foil bearing (HFB) in this paper is a combination of a traditional hydrodynamic foil bearing with externally pressurized air/gas supply system to enhance load capacity during the start and to improve thermal stability of the bearing. The HFB is more suitable for relatively large and heavy rotors where rotor weight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…(i) Studies on subsynchronous vibration due to nonconservative gas film forces [31][32][33][34][35] (ii) Studies on synchronous and supersynchronous vibration due to rotor rotation [36][37][38][39] (iii) Studies on the system response to harmonic vibration and shock [40][41][42][43][44] Although most vibration studies have focused on these three categories, in the real world, systems are often subjected to random vibrations from the environment, especially in in-vehicle devices, where the forces acting on vehicles traveling over irregular terrain are usually modeled as random vibrations [45]. Random vibrations are vibrations that cannot be described by a deterministic function, such as bumps in a vehicle's path and vibrations in an aircraft fuselage due to atmospheric turbulence [46], and random vibrations have been shown to have destructive effects on many devices [45,47].…”
Section: Introductionmentioning
confidence: 99%
“…(i) Studies on subsynchronous vibration due to nonconservative gas film forces [31][32][33][34][35] (ii) Studies on synchronous and supersynchronous vibration due to rotor rotation [36][37][38][39] (iii) Studies on the system response to harmonic vibration and shock [40][41][42][43][44] Although most vibration studies have focused on these three categories, in the real world, systems are often subjected to random vibrations from the environment, especially in in-vehicle devices, where the forces acting on vehicles traveling over irregular terrain are usually modeled as random vibrations [45]. Random vibrations are vibrations that cannot be described by a deterministic function, such as bumps in a vehicle's path and vibrations in an aircraft fuselage due to atmospheric turbulence [46], and random vibrations have been shown to have destructive effects on many devices [45,47].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic response along the horizontal and vertical directions was analyzed using the system state trajectory, Poincare diagram, power spectrum, and bifurcation plot. Kim et al [36] obtained the impact response of GFJB from an external 5.55 g load of lateral acceleration. It was found that there was synchronous vibration and sub-synchronous vibration in the rotor supported by the foils.…”
Section: Introductionmentioning
confidence: 99%